LncRNA HOTAIR regulates cell invasion and migration in endometriosis through miR-519b-3p/PRRG4 pathway - Bao, Qiufang; Zheng, Qiaomei; Wang, Shaoyu; Tang, Wenlu; Zhang, Bin (Frontiers in Oncology, 2022)
Endometriosis is a common benign disease in gynecology and has malignant biological behavior, such as hyperplasia, invasion, metastasis, and recurrence. However, the pathogenesis of endometriosis remains unclear. The present study aimed to investigate whether LncRNA HOTAIR regulates cell invasion and migration in endometriosis by regulating the miR-519b-3p/PRRG4 pathway. The qRT-PCR results showed that the average relative expression of LncRNA HOTAIR was much higher in ectopic endometrial tissues than in eutopic endometrial tissues. Scratch and transwell assays showed that the cell migration and invasion ability of LncRNA HOTAIR overexpression group were significantly higher than those in the control group. Conversely, the LncRNA HOTAIR knockdown group showed the opposite results. Bioinformatics analysis suggested that the downstream target genes of LncRNA HOTAIR were miR-519b-3p and PRRG4. Knockdown of LncRNA HOTAIR can reduce the up-regulation of PRRG4 by miR-519b-3p and then inhibit the invasion and migration ability of endometrial stromal cells. In Conclusion, LncRNA HOTAIR can regulate the ability of invasion and migration of endometrial stromal cells, and its mechanism is proved by regulating the miR-519b-3p/PRRG4 pathway.